THE COMPUTATION OF DESCRIPTION GRAMMARS - Stouffs, Rudi (CAADRIA-ASSOC COMPUTER-AIDED ARCHITECTURAL DESIGN RESEARCH ASIA, 2021)
21st International Conference on Computer-Aided Architectural Design Research in Asia (CAADRIA)